If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 3 + 2x Solving 25 = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 25 + -2x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 25 + -2x = 3 + 0 25 + -2x = 3 Add '-25' to each side of the equation. 25 + -25 + -2x = 3 + -25 Combine like terms: 25 + -25 = 0 0 + -2x = 3 + -25 -2x = 3 + -25 Combine like terms: 3 + -25 = -22 -2x = -22 Divide each side by '-2'. x = 11 Simplifying x = 11
| 8x+100=180 | | 14c+7=35 | | 5n+14=164 | | (x^2+2*y^2)dx+(2*x^2+y^2)dy=0 | | 3x-Y=-27 | | 33=2X+17 | | h(x)=(0)2+3x+-18x | | 4x^2+80=26x | | 8y=36-4y | | h(x)=(0)2+3x+-18 | | 5x-13=4x | | -22+2n=-8(3n+7) | | 5x+3y-4=30 | | log(7-12x)=2 | | 1+3y-y=y-4+2y | | 5y+3y-4=30 | | 6.2x+7.1x-y= | | Y=40x+-16x^2 | | .4y+7.96=2.24 | | (x+4y^2)dy+(y+x^2)dx=0 | | 28x^2-9x-1=0 | | 3x+13=-3x+73 | | (2v+14)(v^2-8v+12)=0 | | 14t+15=10t+31 | | 8x-1=642x | | 2t-7=t+2 | | z^2+(4+i)*z-6+6i=0 | | 6h+20=720 | | 2b-50+b+2b-2+30+b-25+44+b-22=360 | | 2n-15=45 | | -3(4+2)=4-22 | | 4n+12=7n+9 |